2007
DOI: 10.1016/j.chroma.2006.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Nonaqueous capillary electrophoretic behavior of 2-aryl propionic acids in the presence of an achiral ionic liquid

Abstract: Ionic liquids (ILs) appear really attractive as electrolyte additives in nonaqueous capillary electrophoresis (NACE). These salts may offer new possibilities of interactions to modulate analyte effective mobilities. The presence of 1-n-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (BMIM NTf2) in acetonitrile/alcohol background electrolytes (BGEs) was investigated in this work. The aim of this study was to elucidate the influence of the IL concentration on the electrophoretic behavior of four ary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…As shown in Fig. 10 26.5 cm/50 lm 3.5 -4.0 min [103] polyphenols are retarded, taking a longer time for elution because they may associate either with the positively charged imidazolium groups coating the capillary wall or with the free imidazolium ions present in the running buffer. Again, the separation was postulated to be due to association (i. e., H-bonding, ion-dipole/ion induced-dipole) interactions between the polyphenols and the imidazolium cations.…”
Section: Application Of Ils In Cementioning
confidence: 98%
“…As shown in Fig. 10 26.5 cm/50 lm 3.5 -4.0 min [103] polyphenols are retarded, taking a longer time for elution because they may associate either with the positively charged imidazolium groups coating the capillary wall or with the free imidazolium ions present in the running buffer. Again, the separation was postulated to be due to association (i. e., H-bonding, ion-dipole/ion induced-dipole) interactions between the polyphenols and the imidazolium cations.…”
Section: Application Of Ils In Cementioning
confidence: 98%
“…Switching to the use of electrolyte additives in CE separations of organic acids, Francois et al [122] reported the use of achiral ionic liquids to manipulate electrophoretic mobilities of 2-arylpropionic acids. In their study they were able to describe interactions between the solutes and the ionic liquid, 1-n-butyl-3-methylimidazolium bis(trifluoromethane-sulfonyl)imide, in NACE.…”
Section: Stationary Phases Modified Capillaries and Electrolyte Addmentioning
confidence: 99%
“…Both the cations coated on the capillary walls and the free cations in the BGEs interacted with the analytes (Francois et al, 2007a). The two analytes (Fig.…”
Section: Separation Mechanismmentioning
confidence: 99%